Analisis SWOT Terhadap Strategi Badan Kontak Majelis Taklim (BKMT) dalam Meningkatkan Partisipasi Perempuan dalam Kegiatan Sosial Keagamaan di Kabupaten Padang Lawas Utara - Dhifa Yunisa Mei da Hasibuan; Khatibah Khatibah; Ahmad Sujai Tanjung; Ikhwan Kurnia Hutasuhut (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT This study aims to determine the strategy of Badan Kontak Majelis Taklim (BKMT) in promoting women’s participation in socio-religious activities in Padang Lawas Utara Regency. Using a descriptive qualitative approach, data were collected through three sources: field observation, in-depth interviews with BKMT officials and members, and organizational document review, then analyzed through data condensation, presentation, and conclusion drawing supported by source and method triangulation. The findings focus on women's high participation during activity implementation, with a stable 75–80% attendance rate. Based on SWOT analysis, BKMT's strengths lie in religious awareness and social cohesion. However, involvement in strategic decision-making is still hindered by customary norms, unequal information, and limited regional coverage. BKMT can become an inclusive space if members' roles in decision-making are expanded. Keywords: SWOT Analysis; Organizational Strategy; Women's Participation.